Control of Conventionality and Protection of Civil Rights in Colombia - Cabrera-Suárez, Lizandro Alfonso (DIXI, 2014)
The Colombian State has committed itself to compliance on human rights in terms of adapting ordinary laws to the contents of the block of constitutionality. Thse policies must be designed, regulated, chosen and applied to the human rights enshrined in international agreements and treaties ratifid by Colombia, thus the importance of compliance by the guerrillas with humanitarian norms. Th government has stated that, lacking any possibility for coercion, now would be the time for the guerrillas to demonstrate their commitment to peace by complying with those precepts. Tht is because it would be easier to arrive at a negotiated political solution to the conflct by means of a bilateral cease-fie or truce, or, failing this, through a war regulated by the norms of international humanitarian law, because in a conflct as degraded as Colombia’s, this becomes more complex. Ths research work is based on the dualistic theory,insofar as Article 93 of the Colombian Constitution establishes that international treaties and agreements ratifid by the Congress, which recognize human rights and prohibit their limitation in states of emergency, prevail in the internal order. Ths the rights and duties enshrined in the Constitution shall be interpreted according to the international human rights treaties ratifid by Colombia.
Keywords: block of constitutionality; control of conventionality; Constitutional Court; human rights; international treaties; principles.